Aggregated conceptual model of sediment transport for mountain basins in Antioquia- Colombia (2016)
An aggregated model to estimate mean denudation rates of tropical mountain basins with limited data is presented, which is calibrated for Antioquia (Colombia); based on the transport equation of Engelund-Hansen. Two complementary approaches are purposed: (1) alluvial river reach model, dependent on discharge, slope and hydraulic geometry and (2) hillslope model dependent on discharge minus base flow, slope, drainage density and flow convergence degree. Both models are closed with a regression for the Shields parameter, depending on sediment yield (t/km2/yr) and an erodibility factor, which is considered robust due to the diversity of scale, morphology and weather of the 23 basins analyzed. Both model approaches predicts inside a +/- 50% margin of error the sediment yields of 70% of the basins, those with less peculiarities; correcting it with a bed load portion, additional to the suspended transport measured, analytically estimated and proved with field data.